Additive manufacturing and 3D printing technology principles and applications - Awari, G. K.; Thorat, C. S.; Ambade, Vishwjeet; Kothari, D. P. 1944- (CRC Pres, Taylor & Francis Group, 2021)
Additive Manufacturing and 3D Printing Technology: Principles and Applications consists of the construction and working details of all modern additive manufacturing and 3D-printing technology processes and machines, while also including the fundamentals, for a well-rounded educational experience. The book is written to help the reader understand the fundamentals of the systems. This book provides a selection of additive manufacturing techniques suitable for near-term application with enough technical background to understand the domain, its applicability, and to consider variations to suit technical and organizational constraints. It highlights new innovative 3D-printing systems, presents a view of 4D printing, and promotes a vision of additive manufacturing and applications toward modern manufacturing engineering practices. With the block diagrams, self-explanatory figures, chapter exercises, and photographs of lab-developed prototypes, along with case studies, this new textbook will be useful to students studying courses in Mechanical, Production, Design, Mechatronics, and Electrical Engineering